2015
DOI: 10.1186/s13660-015-0696-2
|View full text |Cite
|
Sign up to set email alerts
|

New upper bounds for ∥ A − 1 ∥ ∞ of strictly diagonally dominant M-matrices

Abstract: A new upper bound for the infinity norm of inverse matrix of a strictly diagonally dominant M-matrix is given, and the lower bound for the minimum eigenvalue of the matrix is obtained. Furthermore, an upper bound for the infinity norm of inverse matrix of a strictly α-diagonally dominant M-matrix is presented. Finally, we give numerical examples to illustrate our results. MSC: 15A42; 15A45

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…For certain specific constants ! ij ; i; j D 1; 2; : : : ; n, Wang, Sun and Zhao (Theorem 2, [137]) have shown that…”
Section: A Chain Conditionmentioning
confidence: 99%
“…For certain specific constants ! ij ; i; j D 1; 2; : : : ; n, Wang, Sun and Zhao (Theorem 2, [137]) have shown that…”
Section: A Chain Conditionmentioning
confidence: 99%
“…Various authors have recently studied the family of w.c.d.d. M-matrices, obtaining bounds on the infinity norm of their inverses (i.e., A −1 ∞ ) [19,5,14,23,10]. While a w.c.d.d.…”
Section: Introductionmentioning
confidence: 99%
“…But it is difficult to determine nonsingular H − matrices in practice. The problem is investigated in some papers, (see [3][4][5][6][7][8][9][10][11]). In this paper, we obtain a practical criterion of H − matrices.…”
Section: Introductionmentioning
confidence: 99%